PERILAKU KONSUMEN DALAM BERPINDAH MEREK PRODUK SEPEDA MOTOR - Khusniyah Purwani (Jurnal Aplikasi Bisnis, 2017)
This research ofbrand switching consumer behavior in motorcycle products focused on getting of consideration setsize consumer. The results showed that the replicated research model wasfit enough to be applied to the observed data. This condition indicated that brand switching consumer behavior occurred because of variables of the research. Four factors of getting of consideration set size consumer in the model com prised 1) product knowledge, 2) media search, 3) satisfaction and 4) prior experience.